Dissolution Incompatibility of Paracetamol as a Silent Dissolution Retardent Of Concomitantly Administered Drugs - Yasarathna, K.; Wijesinghe, C.; Jayasuriya, B.; Pathirana, W. (My University, 2017)
High strength tablets containing 500 mg or more active ingredients could affect the dissolution of concomitantly administered drugs. Dissolution of ten generic solid dosage forms was determined in the presence of sodium bicarbonate and paracetamol, 500 – 2250 mg. In a total of 111 dissolution tests 41 failed (37%) to meet the criteria. Where paracetamol was present 36 out of 50 end points failed (72%) with an extreme case in diltiazem tablets with 0% dissolution. Since longest test end points with failures mostly range from 60 – 90 minutes it is advisable to administer paracetamol 1.5 hours after other drugs in order to avoid potential pharmacokinetic disturbances.
Keywords: Dissolution incompatibility, paracetamol, sodium bicarbonate, diltiazem.